Vietnamese English Teachers’ Perceptions of Culture in ELT Materials in Vietnamese Universities - Do Lan Phuong (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2020)
As one of the main purposes of using English today is for international communication and globalisation, English has been mainly used among bilingual speakers of English who come from different ethnic and cultural backgrounds (McKay, 2006; Sharifian, 2014). In such multinational and multicultural contexts, today English learners have to deal with not only linguistic barrier, but also cultural barrier. Therefore, it is crucially important that they are provided with multicultural knowledge and cross-cultural awareness. However, so far, there has been little research into the perceptions of English teachers towards culture used in ELT materials in EFL contexts. Therefore, the research aims to identify how seven Vietnamese teachers of English in two universities in Hanoi, Vietnam perceived culture and the role of culture in language teaching. This paper also seeks to explore how their perceptions influenced the way they taught culture in their English class and the way they adapted and developed ELT materials for their students with the hope that it will provide useful and practical suggestions for developing appropriate ELT materials for EFL teaching contexts. The research is based on a qualitative research which applies mostly in-depth, semi-structured interviews and document analysis. The data of this research reveals that most participants recognized the close and interrelated relationship between language and culture and the crucial role of culture in language teaching. They also identified the important role of English as an international language and cultural differences in ELT materials. Realizing a cultural gap in most of the materials they taught, they tried to adapt the materials based on their students’ needs.